Annotated translation of a notarial act of civil marriage from Spanish into Arabic - Soto Aranda, Beatriz; Kabbour, Rabab (Anaquel de Estudios Árabes, 2020)
The Spanish civil marriage notarial acts stem from Law 15/2015 of 2 July 2015 of the Voluntary Jurisdiction. Up to then, voluntary jurisdiction acts could only be performed by judges, however, since the entry into force of Law 15/2015, notary publics, in their capacity as jurists, can intervene in some of these acts, such as a marriage act, with full effectiveness. This has led to a diversification of the type of documents that are translated into Arabic to prove the marital status of a citizen residing in Spain - documents such as marriage certificates, which are issued by the Civil Registry, and de facto union certificates, which are a matter of Autonomous Communities competence, and do not depend on state regulation.This paper presents a commented translation into Arabic of this type of legal-administrative documents, paying special attention to the linguistics, legal and cultural knowledge that this type of specialized translation requires. And it focuses as well in the macro-structures of both the original and the target texts.  Finally, regarding the terminology and formal aspects stipulated by law in the target legal system, given the differences between the Arab legal systems, and since this is not a comparative study, Morocco has been selected as the reception context of a hypothetical translation order, as this is the Arab country with the largest number of immigrants in Spain.
Keywords: notarial acts; legal translation; Spanish; Arabic